Cyclisation cascades via reactive iminium intermediates - Gregory, AW (2014)
The aim of this D.Phil was to develop a range of cyclisation cascades, which initially form a reactive iminium intermediates that can then be attacked by a pendant nucleophile resulting in novel polycyclic structures. This concept has been applied to the development of three methodologies and has resulted in the discovery of new reactivity as well as the synthesis of a wide range of interesting novel structures Chapter 1: Enantioselective chiral-BINOL-phosphoric acid catalysed reaction cascade A highly enantioselective hydroamination / N-sulfonyliminium cyclisation cascade using a combination of Au(I) and chiral phosphoric acid catalysts has been developed. Proceeding by an initial 5-exo-dig hydroamination and a subsequent phosphoric acid catalysed Pictet- Spengler cyclisation, the reaction provides access to complex sulfonamide scaffolds in excellent yields and with high levels of enantiocontrol. The scope can be extended to lactam derivatives, with excellent yields and enantiomeric excesses of up to 93% ee. Chapter 2: Iridium catalysed nitro-Mannich cyclisation A new chemoselective reductive nitro-Mannich cyclisation reaction sequence of nitroalkyltethered lactams has been developed. An initial rapid and chemoselective iridium(I) catalysed reduction of lactams to the corresponding enamine is subsequently followed by intra molecular nitro-Mannich cyclisation. This methodology provides direct access to important alkaloid, natural product-like structures in yields up to 81% and in diastereoselectivities that are typically good to excellent. An in-depth understanding of the reaction mechanism has been gained through NMR studies and characterisation of reaction intermediates. The new methodology has been applied to the total synthesis of (±)-epi-epiquinamide in 4 steps. Chapter 3: Iridium catalysed reductive interrupted Pictet-Spengler cyclisation A novel reductive interrupted Pictet-Spengler cyclisation reaction cascade has been created. An iridium(I) catalyzed partial reduction of lactams/amides to the corresponding iminium is subsequently trapped by a pendant indole nucleophile. Interruption of the Pictet-Spengler reaction by indolium reduction provides a wide range of novel spirocyclic indoline moieties in excellent yield and diastereoselectivity.